(untitled) (Bangladesh Journal of Urology, 2022)
Background: The exact mechanism of fever after PCNL has not been established.2. This research studied the frequency of post-PCNL fever and UTI in both initial preoperative positive and negative urine culture group of patients. Objectives: To compare the frequency of post PCNL fever and UTI in initial positive and negative preoperative urine culture patients. Method: This was a prospective observational study on a total sixty patients who underwent single PCNL at the Department of Urology, Sir Salimullah Medical College Mitford Hospital, Dhaka and National Institute of Kidney Diseases and Urology, Dhaka from March 2013 to October 2014.There were two groups of patients, Group-I, with initial positive preoperative urine culture and another Group-II with initial negative preoperative urine culture. But the operation deferred until the positive urine culture became negative. Both groups received prophylactic antibiotic. Results: The frequency of fever and UTI after PCNL was 53.33% in Group-I (n=30) but only 23.33% was found in Group-II (n=30).Significant correlations were observed between post-PCNL fever with initial positive preoperative urine culture group (p=0.017), female sex (p=0.02), prolong hospital stay (p=0.018). Conclusion: The frequency of postoperative fever and UTI is more than two times in preoperative positive urine culture patients than culture negative patients. Risk of post- PCNL fever increased in patients who had initial positive preoperative urine culture. Bangladesh J. Urol. 2021; 24(1): 25-32